Are fetuses that fail to achieve their growth potential at increased risk of intrapartum compromise?. (October 2015) - Prior, T.; Paramasivam, G.; Bennett, P.; Kumar, S.
Abstract Objective The true growth potential of a fetus is difficult to predict but recently a new definition, independent of fetal weight, using cerebroplacental (cerebro‐umbilical) ratio (CPR) < 0.6765 multiples of the median (MoM), was reported. We applied this definition to a cohort of low‐risk pregnancies recruited prospectively to determine if fetuses with CPR < 0.6765 are at increased risk of developing signs of intrapartum fetal compromise. Methods Recruitment to this prospective observational study took place between March 2011 and March 2014. All women with low‐risk singleton pregnancies at term were eligible. Women with known or suspected placental dysfunction were excluded, as were women with fetuses with an estimated fetal weight < 10th centile. All participants underwent ultrasound examination prior to active labor (≤ 4 cm cervical dilatation), during which fetal biometry as well as umbilical artery and fetal middle cerebral artery blood flow were assessed. Following delivery, intrapartum and neonatal outcomes were compared between fetuses that had a CPR < 0.6765 MoM and those that had a CPR ≥ 0.6765 MoM. Results In total, 775 women were recruited. Fetuses with CPR < 0.6765 MoM were significantly more likely to require Cesarean delivery because of presumed fetal compromise (P < 0.001). These fetuses were also at increased risk of compromise at any time during labor and were less likely to be delivered vaginally, spontaneously or otherwise, than were those with CPR ≥ 0.6765 MoM. CPR < 0.6765 MoM gave a positive predictive value (PPV) for Cesarean delivery because of presumed fetal compromise of 36.7% and a negative predictive value of 88.7%, with a sensitivity of 18% and a specificity of 95.4%. Conclusion Fetuses that failed to achieve their growth potential (defined as CPR < 0.6765 MoM) were at increased risk of intrapartum compromise and were less likely to be delivered vaginally. However, a low negative predictive value was observed for fetal compromise and further studies are required to support the translation of this technique into clinical practice. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.